Innovative surgical and stress-stimulated rat model of ligamentum flavum hypertrophy - Chen, Long; Zhang, Zhaoyuan; Li, Niandong; Zhang, Wanxia; Zheng, Zhouhang; Zhang, Yu (Frontiers in Veterinary Science, 2025)
Background and purposeAnimal models of LFH are still in the exploratory stage. This study aimed to establish a reliable, efficient, and economical model of LFH in rats for the study of human ligamentum flavum (LF) pathological mechanisms, drug screening, development, improvement of surgical treatment, disease prevention, and other aspects.Methods and materialsForty rats were divided into an experimental group and a sham group of 20 rats. The experimental group (n = 20) was treated with an innovative operation combined with stress stimulation at the L5-L6 segments, the L5 and L6 spinous processes, transverse processes, and supraspinous ligaments were excised, along with removal of the paraspinal muscles at the L5-L6 level. One week after surgery, the rats were subjected to slow treadmill running daily. In the experimental group (n = 20), the spinous process, transverse process, supraspinous ligament and paraspinous muscle of L5 and L6 were excised. And for a week after the surgery, the rats ran on a treadmill at a slow pace every day. While the sham group (n = 20) was treated with sham operation only. Seven weeks later, MRI, immunohistochemistry (IHC), and western blot (WB) will be performed on the LF of the L5-6 segment in the two groups of rats.ResultsMRI results showed that the LF in the experimental group was significantly thicker than that in the sham group. Masson staining results indicated that LF thickness, collagen fiber area, and collagen volume fraction (CVF) were significantly higher in the experimental group than in the sham group. IHC and WB showed that the expression of TGF-β1, COL1, and IL-1β in the LF of the experimental group was significantly higher than that in the LF of sham group.ConclusionThrough innovative surgical intervention combined with stress stimulation, a relatively reliable, efficient, and convenient rat LFH model was established.